ADHD among Indonesian Primary School Students: Measurement and Prevalence - Supra Wimbarti; Sri Kusrohmaniah (Universitas Ahmad Dahlan, 2023)
In Indonesia, adequate screening instruments for the early detection of attention deficit and hyperactivity disorder (ADHD) in primary school students is not available prior to the study. We aimed to assess the Indonesian version of the Conners 3 Teacher Rating Scale (Conners 3-T) in an Indonesian setting and assess the prevalence of ADHD in primary school children. The study participants comprised 314 primary school students aged 6-12 years old. Conners 3-T was translated from English to Bahasa Indonesia and back-translated into English. Those students suspected of ADHD were further diagnosed by a senior child psychologist for diagnosis.